MODERATING EFFECT OF SWITHCING COST ON RELATIONSHIP BETWEEN PERCEIVED VALUE, SATISFACTION, TRUST ON LOYALITY OF YOUNG-AGE CUSTOMER IN TOKOPEDIA - Margaretha Pink Berlianto (UBL, 2016)
The development of Internet has changed the way consumers purchase goods and services which lead to the rapid growth of e-commerce. In e-commerce, competition might occur in just one click, which raises a question whether the switching cost could be an obstacle for e-commerces in gaining customer loyalty. The purpose of this study is to analyze customer perceived value, customer satisfaction and trust on Tokopedia’s young customers with switching cost as moderator variable on customer loyalty. Customer satisfaction variable consists of five dimensions. There are customer services, order fulfillment, Ease of Use, Product portfolio and security and privacy. This research carried out on young Tokopedia customers living in Jakarta and Tangerang area. The data collection was done by distributing 300 questionnaires to under graduated students. Variables are measured with 5-point Likert scale. Validity testing using factor loading value of ≤ 0.6, Reliability test using the composite reliability with value ≥ 0.7, Cronbach's alpha> 0.7, and the average variance extracted > 0.50. In this study, there are seven hypotheses to be tested. The model fit and hypothesis testing will be done by using PLS analysis in SmartPLS 3.0 software. From seven hypotheses, 6 hypothesis are accepted and 1 hypothesis are rejected. The result findings suggest that Tokopedia management needs to take attention to customer satisfaction. Even though the customers are satisfied but it doesn’t lead them to be a loyalcustomers. Dimension of customer service and privacy showed a small mean value from the other dimensions. Tokopedia management should concern more to improve these dimension so can increase customer loyalty.